Comic Representation of Life Experience in German Aphorisms. - Zubach, Oksana A. (My University, 2024)
Humor as an element of the laughing culture of the linguistic and cultural space illuminates the collective consciousness of the people, the values that are transmitted from generation to generation (norms, customs, moral and ethical preferences) and create life experience. An aphorism is an author's statement that compresses the personal and social life of a person and is the most enduring microform of all as a medium of communication and method of thinking (Hui, A., 2019). The purpose of aphorisms is to express a point or illustrate a commonly held belief (Khairy, N. A., Saeed, M., 2012). Aphoristic "rhetoric of suggestion" (Fricke, H., 1992) makes you think about the truth of the content, check it, agree or deny it. Their intentional specificity constantly requires cognitive activity and appeal to one's own experience. The comic effect in terms of content and expression is traced through the effect of surprise/non-expectation, incitement to reflection, reasoning, making analogies, expressing agreement or denial